Building a Model of the Influence of Information Technology Usage, Technology Competence, and Technostress on Lecturer Performance in the Digital Age - Kurniawan, Dian; Rinandiyana, Lucky Radi; Mufreni, Alfin Nurfahmi; Budiman, Asep; Kurniawati, Ane; Badriatin, Tine (Future Science, 2024)
Universities must carry out digital transformation in the era of the Industrial Revolution 4.0 and Society 5.0. The application of infor-mation technology brings the hope of increasing lecturer performance and ultimately improving student quality. The use of information technology and lecturer technological competence will help achieve optimal performance. The demands of the application of information technology are thought to cause a new phenomenon known as